Potensi Vegetasi Hutan Mangrove untuk Mitigasi Intrusi Air Laut di Pulau Kecil - Cahya Damayanti; Rian Amukti; Suyadi, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Mangrove Forest Vegetation Potency to Mitigate Seawater Intrusion on Small Island. Natural resources exploitation in the coastal areascaused serious problems for shallow ground wateravailabily especially in small islands. Small islands society such as in Ambon Island facesdrinking water quality degradation due to the sea water intrusion.Mangrove is one of the coastal ecosystemtypesthatis though to minimize sea water intrusion.However, the information about mangroveparametersthat can be used todetermine the mangrove forest patches potency in small islands to mitigate sea water intrusion is still limited. The aim ofthis study is to assess the correlationof mangrove vegetation and sea water intrusion using transect anddipole-dipole configuration geoelectric methods. The study showed that the thickness of mangrove vegetation and the size of mangrove trees determined the mangrove forest potencyto mitigatesea water intrusion.There was no sea water intrusion (relativity values:75.5-118 Wm)in Passo, due to thick mangrove vegetation (mean:320 m) and bigmangrove tree sizes (mean diameter: 19cm and mean height: 10m).Sea water intrusion was low (relativity values: 0.798-4.53Wm)in Poka due to thin mangrove vegetation (mean 10-100 m) and small tree sizes(mean diameter: 8.6cm and mean height: 5m). In contrasts, sea water intrusion was very high (relativity values: 1.4-9.2Wm) for the areas without mangrove vegetation(e.g. Lateri). These mangrove parameters were also negatively correlated with the distribution and coverage area of sea water intrusion.Mangrove patches in small islands can be used assea water intrusion mitigation tools, but theecosystem condition was already degraded or in the poor conditions. The findings of this study are useful for government as a basis in decision makingand to better manage of ground water and coastal ecosystem particularly mangrove.